Reviewing the Conditions for Business Tourism in Bulgaria - Ianeva, Mariana; Georgieva, Ralitsa (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2020)
This report outlines the trends in the development of business tourism in Bulgaria and analyzes the conditions for doing business tourism in the country. The main results of the study relate to the general theory about the specificity of the business tourism, the analysis of the practical application of tendencies of the different subjects at macro and micro level. In the specific studies and in drawing up the conclusions from them, common scientific methods as observation, analysis, synthesis, analogy and others, are applied.